Obligations and Responsibilities of Notaries in Providing Social Services to The Community as Public Officials - Atmoko, Dwi; Sri Darmadi, Nanang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
At present, where economic development is increasingly rapid and supported by increasingly developing technology and the increasingly dense population in Indonesia, this country has various and varied problems. Likewise with its diverse society where in reality the economic gap between the able and the unable has its own burden for the person concerned and also the state. In its journey, especially for those who are unable, of course, they also need a notary in achieving their desires, especially regarding the certainty and validity of a letter regarding their assets or related to certain agreements. The role of a notary is needed in society, especially for those who are unable to get their desires for free as mandated in the Notary Law (UUJN) Article 37 paragraph (1) which states that